Il Piedistallo Vuoto : Fantasmi dall'Est Europa - Scotini, Marco; Buden, Boris; Chukhrov, Keti; Havranek, Vit; Warsza, Joanna; Museo Civico Archeologico, Bologna (Bologna : Mousse Publishing, 2014)
Abramovic, Marina ; Akhunov, Vyacheslav ; Alimpiev, Victor ; Althamer, Pawel ; Antufiev, Evgeny ; Atabekov, Said ; Avotins, Janis ; Balka, Miroslaw ; Cantor, Mircea ; Didziapetris, Gintaras ; Djordjadze, Thea ; Feriancova, Petra ; Friedman, Yona ; Grigorescu, Ion ; Grubic, Igor ; Gutov, Dmitry ; Halilaj, Petrit ; Jasansky, Lukas ; Polak, Martin ; Kabakov, Ilya & Emilia ; Koller, Julius ; Kovanda, Jiri ; Kovylina, Elena ; Kusmirowski, Robert ; Lulaj, Armando ; Maljkovic, David ; Man, Victor ; Martek, Vlado ; Meldibekov, Yerbossyn ; Mikhailov, Ivan ; MoAA (Dorothy Miller) ; Muresan, Ciprian ; Narkevicius, Deimantas ; Ondak, Roman ; Paci, Adrian ; Putrih, Tobias ; Sala, Anri ; Seda, Katerina ; Solakov, Nedko ; Sosnowka, Monika ; Turba, Tamas St. ; Ter-Oganyan, David ; Galkina, Alexandra ; Tichy, Miroslav ; Toomik, Jaan ; Trbuljak, Goran ; Zmijewski, Artur
Arte Fiera Collezionismi : Il Piedistallo Vuoto : Fantasmi dall'Est Europa, Museo Civico Archeologico, Bologna, 24 January - 16 March, 2014
boek
Keywords: Oost-Europa